POPULARIZING AMERICAN PROFESSIONAL WRESTLING AS POPULAR CULTURE OUTSIDE THE UNITED STATES - Raisa Hani Tamara; Bhakti S Nugroho (CrossOver, 2021)
This research is under Transnational American Studies, which focuses on the popularity of American professional wrestling outside the United States. Nowadays, as popular culture, American professional wrestling is not only mainly consumed within North America but also consumed by massive viewers around the world. For instance, in recent years, American professional wrestling has expanded in Saudi Arabia and India. However, it fails to conquer Indonesian viewers. Thus, studies of the popularity of American wrestling as popular culture outside the United States are needed due to its massive social, cultural, and economic impacts. This research studies the recent popularity of professional wrestling outside the United States by taking  the sample from Saudi Arabia, India, and Indonesia, which Glenday considers as ‘outside wrestling culture territory’. In popularizing American professional wrestling as popular culture, three crucial factors support disseminating this popular culture outside the United States: cultural attachment, media power, and government involvement. Cultural attachment relies on cultural sameness (in this case, same ‘wrestling culture’) that later creates people’s enthusiasm. Media functions as a tool to disseminate this popular culture.  Then, government involvement emphasizes the openness of one country toward American professional wrestling, which consists of violent content. Those three factors become essential parts of popularizing American professional wrestling outside the United States. Cultural attachment, in this case, is the most influential factor in the rise of American professional wrestling popularity outside the United States.     Keywords: popular culture, professional wrestling, transnational.